Finite element model to simulate impact on a soft tissue simulant - Imam, S. A.; Hughes, A. C.; Carré, M. J.; Driscoll, H.; Winwood, K.; Venkatraman, P.; Allen, T. (Sports Engineering, 2023)
A finite element model of an impact test on a soft tissue simulant, used as part of a shoulder surrogate, was developed in Ansys© LS-DYNA®. The surrogate consisted of a metal hemicylindrical core, with a diameter of 75 mm, covered with a 15 mm thick relaxed muscle simulant. The muscle simulant consisted of a 14 mm thick layer of silicone covered with 1 mm thick chamois leather to represent skin. The material properties of the silicone were obtained via quasi-static compression testing (curve fit with hyperelastic models) and compressive stress relaxation testing (curve fit with a Prony series). Outputs of the finite element models were compared against experimental data from impact tests on the shoulder surrogate at energies of 4.9, 9.8 and 14.7 J. The accuracy of the finite element models was assessed using four parameters: peak impact force, maximum deformation, impact duration and impulse. A 5-parameter Mooney-Rivlin material model combined with a 2-term Prony series was found to be suitable for modelling the soft tissue simulant of the shoulder surrogate. This model had under 10% overall mean deviation from the experimental values for the four assessment parameters across the three impact energies. Overall, the model provided a repeatable test method that can be adapted to help predict injuries to skin tissue and the performance/efficacy of personal protective equipment.